Pemberdayaan Guru terhadap Penurunan Indeks Plak - Asio Asio (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2015)
The reseach is to find out whether through teacher empowerment can reduce plaque index. Experimental research design of pre-test and post-test control group design respondents 18 respondents. Class V number of 56 respondents SDN experimental and control group 77 number of 51 respondents. Wilcoxon test results showed no significant difference before and after the training of 18 respondents classroom teachers SDN 74 / p value0.0001. There was a highly significant difference plaque index 51 PHP class respondents SDN 74sebelum and after counseling by an independent teacher p value 0.0001. The difference in plaque index difference of 51 respondents PHP fifth grade students of SDN 74 experimental group control group, p 0.0001. There is a decrease in the influence of teacher empowerment on child plaque index class V students of SDN 74 / IV Jambi..